Pemodelan Struktural Prediktor Perilaku dan Strategi Prioritas Pemangku Kepentingan untuk Konsumsi Hijau di Kalangan Pemuda Indonesia - Maya Maria; Anisa Zahwa Akbara; Ginta Ginting (Society, 2025)
This study examines the behavioral determinants and strategic enablers of green consumption among Indonesian youth, aligning with Sustainable Development Goal 12: Responsible Consumption and Production. Employing a mixed-methods approach, the research integrates structural modeling via partial least squares structural equation modeling (PLS-SEM) with multi-stakeholder prioritization through the Analytic Hierarchy Process (AHP). Quantitative data collected from 229 respondents aged 18–35 indicate that attitude (? = 0.89), perceived behavioral control (? = 0.16), and actual behavior (? = 0.70) significantly influence the willingness to engage in green consumption. Interestingly, perceived behavioral control also exerts a negative effect (? = –0.58), pointing to possible psychological or systemic constraints. Complementary qualitative insights were obtained from focus group discussions involving 25 stakeholders representing government agencies, non-governmental organizations, academia, and the private sector. These discussions identified and ranked key sustainability strategies, with top priorities including the integration of environmental topics into formal education, the expansion of eco-friendly public infrastructure, and the enhancement of youth-focused awareness campaigns. The findings underscore the dual necessity of fostering individual behavioral intentions and providing institutional support through coordinated stakeholder action. This study offers evidence-based recommendations for policymakers, educators, and industry actors to strengthen youth engagement in sustainable consumption initiatives.